Analysis of Rehospitalization of Preterm and Term Infants in First Month of Life - Athba Alaa Madhloom; Sijal Fadhil Farhood Al-Joborae (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: rehospitalization of preterm and term neonates was planned readmission to the hospital within30 days post birth discharge prematurity is the main reasons of neonatal illness and death in concentratedcare units universal. The aim of study to study the reasons of rehospitalization of preterm plus term infantsin first month of life and analyze the reasons of rehospitalization in relation to infantile and maternal sociodemographicand medical characteristics. Method: It is descriptive cross sectional study in hospital on200 preterm and term infants who were be concerned in the neonatal care units in Babylon Maternityand Pediatrics Hospital, Imam Sadik General Teaching Hospital. Results: 200 cases of preterm and termneonates were screened and enrolled in the study. The mean and standard deviation of current maternal ageand maternal age at marriage in year were (25.88 ± 7.89) , (20.82 ± 5.56) respectively. 45% of neonateswith birth weight less than 2500 Kg, 48.5% of neonates with gestational age of less than 37 weeks, 35% ofneonates were admitted due to prematurity at first admission , 53.5% of neonatal rehospitalizations was dueto jaundice. The second cause of rehospitalization was infection in 26.5% of neonates, this study found that3.5% of neonatal readmission were due to surgical follow up , 62% of rehospitalized neonates the cause ismedical follow up. Conclusion: Jaundice was the major cause of readmission to hospital in both term andpreterm neonates. The relation between preterm and early admission (particularly for jaundice and feedingproblems) was well documented.